Spanish research in Educational Psychology from a gender perspective (2008-2018) - González-Sala, Francisco; Haba-Osca, Julia; Osca-Lluch, Julia (Anales de Psicología / Annals of Psychology, 2021)
A comparative study disaggregated by gender of the scientific production in Educational Psychology of researchers working in Spanish institutions is carried out. A total of 1949 authors have been identified who have published some work in journals indexed in the Psychology Educational category in the Journal Citation Reports (JCR) corresponding to the years 2008-2018. The 56.44% of the authors identified were women versus 41.92% of men and a 1.64% of authors could not be identified. The results show an increase in the number of papers published in this discipline and an increase in the number of women working in Educational Psychology throughout the period analyzed. However, as a conclusion it could be indicated that in Spanish Educational Psychology there is still no gender equality, especially when the research elite is considered, since among the largest producers there is a greater number of men than women and it is only when analyzing the groups of small and medium producers, where the number of women exceeds that of men. It is essential to deepen and continue carrying out studies that evaluate the evolution and tendencies in a disaggregated way by gender to undertake the necessary corrective measures that allow achieving gender equality.